Michael Powell & Emeric Pressburger's I know where I'm going! - Gray, Allen (<<The>> Criterion Coll., 2001)
A headstrong young woman travels to the Scottish Hebrides to marry a rich industrialist. On the way, she meets a young naval officer and realizes that some things are more important than money.
Bildformat 1.33:1
Orig.: Großbritannien 1945
Enth. audio essay by film historian Ian Christie ; behind-the-scenes stills, narrated by Thelma Schoonmaker Powell ; the 1994 documentary "I know where I'm going! Revisited" by Mark Cousins ; excerpts from Michael Powell's 1937 feature "The edge of the world", with commentary, and the 1978 documentary "Return to the edge of the world" ; photo essay by "I know where I'm going!" aficionado Nancy Franklin, who explores the location used in the film ; home movies from one of Michael Powell's Scottish expeditions, narrated by Thelma Schoonmaker Powell
Keywords: Frau; Gesellschaft; Weltkrieg (1939-1945); Man-woman relationships -- Drama; Women -- Conduct of life -- Drama; World War, 1939-1945 -- Social aspects -- Great Britain; Großbritannien; Hebrides (Scotland) -- Drama; Feature films; Film excerpts; Nonfiction television programs; Romantic comedy films; Video recordings for the hearing impaired